Du cobaye aux nuggets - Frédéric Graber (Revue d'ethnoécologie)
Something happened to chickens during the 20th century, something so massive that they clearly became another kind of animal: broilers today get twice as big in half the time and with half the feeding they needed at the start of the century. This transformation of the broiler is the result of a process of industrialization that happened in most Western countries, but started in the United States and expanded there like nowhere else. This paper presents the major technical innovations that made the industrialization of the broiler possible in the first place and on the specific context of its expansion in the United States during the 20th century.